LISTENING TEXTS AND LISTENING STRETAGIES - Teshaboyeva Nafisa Zubaydulla qizi; Xamidova Mashxura Abror qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: Listening texts, including audio recordings, podcasts, videos, and live conversations, are essential tools in language learning. They expose learners to various accents, speech rates, and communication styles, helping improve listening comprehension. Effective listening strategies, such as predicting content, note-taking, and focusing on keywords, enable learners to better process spoken information. Active listening techniques, like listening for the gist or listening for specific details, enhance learners’ ability to extract meaningful information from diverse auditory inputs. Incorporating varied listening texts and strategies into learning materials fosters adaptability and enhances comprehension skills, preparing learners for real-world language use.